CRIMINOLOGICAL CRITICISM OF CRIMINAL LAW - Todria, Giorgi (European Scientific Journal, ESJ, 2013)
The article discusses the peculiarities of criminal law and criminology. In order to push the process of compulsion on behalf of the state, an individual has to act not as a person who strives to restrain estrangement from the society, but as the one who him/herself causes estrangement. Because of this, the essence of crime for a lawyer is an action of a criminal. Thus, turning an estranged individual into a criminal is a typical example of compulsion on behalf of the state. Owing to this, from the viewpoint of criminal law, the eradication of estrangement can be measured by law-obedience, reducing the number of cases of breaching law, while from the criminological standpoint the eradication of estrangement is measured by improving living conditions, reducing the cases of estrangement.